Educators insights on entrepreneurship education among students / Jazira Anuar, Sairah Saien and Shareenie Shera Abdul Hamid - Anuar, Jazira; Saien, Sairah; Abdul Hamid, Shareenie Shera (2022)
n many educational institutions nowadays, entrepreneurship has emerged as a crucial subject and learning component. In order to cultivate and enhance potential entrepreneurs, entrepreneurship education is being introduced to university students as part of a larger university plan. To create effective entrepreneurship courses, a thorough grasp of knowledge acquired by students to become entrepreneurs is essential. Limited research on the viewpoints of educators regarding their perceptions of student entrepreneurship education has been conducted especially in Malaysia. Hence, this paper explored the perception of educators, focusing on fifteen (15) educators at the Faculty of Hotel & Tourism Management, UiTM Terengganu campus. This study is an exploratory study. Findings derived were indicating knowledge acquired by students, focusing on three (3) themes, including entrepreneurship mindset, market sensitivity, and skills. Students could grow and refine their entrepreneurial skills using the findings as a base. Furthermore, it also contributes to the significance value of strategies that universities can implement for a successful Entrepreneurship Management among students, integrating best practices embedding entrepreneurship skills, market sensitivity and entrepreneurship thinking in enhancing their intention. Recommendations and future research are made based on the findings of the study.